TREATMENT OF REFRACTORY CHRONIC SPONTANEOUS URTICARIA WITH OMALIZUMAB - A REAL LIFE EXPERIENCE - Dašić, Aleksandra (Medical Research, 2022)
Introduction: Patients with refractory chronic spontaneous urticaria (CSU) may pose a significant challenge to the treating physician. Although many studies investigated effects of omalizumab in the refractory CSU, many issues remain unanswered.Aim: To describe our experience in the treatment of refractory CSU with omalizumab in the real-life setting.Material and methods: We retrospectively reviewed charts of patients with refractory CSU treated with omalizumab during a 2-year period.Results: Eight patients with refractory CSU were treated with omalizumab from January 2018 to December 2019. The average duration of CSU was 49.9 months (3-180). A high average 7-day Urticaria Activity Score (UAS7) of 31.3 (12-42) and a low average Urticaria Control Test (UCT) score of 4.1 (0-8) were recorded before omalizumab therapy. Prior to omalizumab, all patients required fourfold dose of  H1-anihistamines, montelukast and corticosteroids to achieve at least partial disease control. Antimalarial was given to two patients and dapsone to three, without the response. Adverse effects of CS were noted in most patients. Patients received 150 mg or 300mg of omalizumab subcutaneously every 4 weeks, for at least 3 months. All patients responded well to omalizumab and discontinued corticosteroid therapy. There were no significant side effects during omalizumab treatment.Conclusion: Omalizumab is effective corticosteroid sparing treatment, enabling disease control in patients with refractory CSU, even in lower doses (150 mg) and when given for a short period. This is especially important when the availability of the drug is determined by economic issues.
Keywords: chronic spontaneous urticaria, refractory, omalizumab